Prevalence of Trichomoniasis in Cervical Cancer Patients - Luh Putu Diah Ayuning; Prawesty Diah Utami; Risma Risma (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Backgroud: Trichomoniasis is the most frequent non-viral sexually transmitted disease in the world, and it can lead to persistent HPV infection. Trichomonas vaginalis infection causes damage to the vaginal mucosa, activation of oncogenes and inactivation of tumor suppressor proteins, and production of non-specific oxidants that lead to cervical cancer. This study aims to determine the prevalence of trichomoniasis in cervical cancer patients. Methods: This study uses systematic literature review method and uses 10 international journals obtained through machine learning and indexed in Scimago.  Journals are screened through PRISMA and have gone through a critical appraisal process.This study took place from April to September 2021.  Results: The prevalence of trichomoniasis in cervical cancer patients ranged from 0.022% to 87.7%, according to the findings of this study. The prevalence results vary due to differences in demographics and diagnostic methods used. Statistical analysis of the association between trichomoniasis and cervical cancer varied between significant and insignificant. Differences in the association are influenced by the research design used, diagnostic methods, and sample of the research. Conclusions: The conclusion of this study is that the prevalence of trichomoniasis in cervical cancer patients was discovered to be the highest in the study by Ghosh et al. in Kolkata, India (72.6% women with CIN 1, 71.0% women with CIN 2 or CIN 3, and 87.7% women with invasive cancer) and the lowest in the study by Su et al.  in Taiwan (0.022%). The association between trichomoniasis and cervical cancer was found to be varied.